2022
DOI: 10.1371/journal.pone.0266867
|View full text |Cite
|
Sign up to set email alerts
|

Patient perceptions by race of educational animations about living kidney donation made for a diverse population

Abstract: Introduction This qualitative study sought to identify potential design and delivery alterations to inform cultural adaptation of educational animations about living donor kidney transplantation (LDKT)–previously developed for a diverse population–to better fit Black Americans’ needs. Methods We conducted a secondary analysis of 88 transcripts derived from interviews and focus groups conducted with diverse target users (62 kidney failure patients, 36 prior/potential don… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Using behaviour change theory within patients’ social support network has been proposed as a key approach to transplant-directed self-management for members of diverse communities [23]. For those who require education around topics such as living kidney donation, Keller et al [24] found that informational content that showed diversity and representation visually (via educational animations) was valuable to recipients.…”
Section: Multi-modal Approachesmentioning
confidence: 99%
“…Using behaviour change theory within patients’ social support network has been proposed as a key approach to transplant-directed self-management for members of diverse communities [23]. For those who require education around topics such as living kidney donation, Keller et al [24] found that informational content that showed diversity and representation visually (via educational animations) was valuable to recipients.…”
Section: Multi-modal Approachesmentioning
confidence: 99%
“…Most of the narratives used in previous work are live-action videos or written texts. Animated narratives have received little attention partially due to the lack of animated health behavior-changing narratives, along with the greater costs of animation production in general (e.g., Keller et al, 2022 ; Winder et al, 2012 ). Almost all animations used in health communication research with children are short non-narrative educational videos instead of the typical entertainment narratives.…”
Section: Narrative Animation and Health Communicationmentioning
confidence: 99%